(untitled) - Dr. Ali Abbas; Muhammad Mahmood Sultan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The purpose of this research piece is to examine the chances and problems that Pakistan’s economy has encountered in light of the country’s rising political unrest. It studies the effects of political unpredictability on economic growth and development and analyses Pakistan’s methods and policies for achieving economic recovery in the face of such difficult conditions. The article uses a variety of academic research and case studies to provide light on the well-known instance of Pakistan’s economic recovery in the face of political unrest. Pakistan, a nation that has gone through political unrest in the past, is today juggling the task of economic recovery with escalating political unrest. This study offers a thorough examination of the complex interplay between political unrest and growth in the economy of Pakistan, putting it forward as a traditional case study. This paper examines the complex dynamics and inter-dependencies between political instability and economic recovery by drawing on a theoretical framework that includes the concepts of political economy, institutional theory, and dependency theory. This study provides a comprehensive analysis of the complex dynamics between political unrest and economic recovery in Pakistan. By understanding these interdependencies, policymakers can formulate targeted strategies to navigate challenges and foster long-term economic stability and development.